2016
DOI: 10.1515/dmpt-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

1846G>A polymorphism ofCYP2D6gene and extrapyramidal side effects during antipsychotic therapy among Russians and Tatars: a pilot study

Abstract: Further well-designed pharmacogenetic studies in different Russian regions are needed to improve psychotropic therapy safety and to establish evidence-based indications for pharmacogenetic testing in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We excluded 20 studies that showed positive associations with AP-induced movement disorders without differentiating with which ones [ 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…We excluded 20 studies that showed positive associations with AP-induced movement disorders without differentiating with which ones [ 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…9 Although a great number of CYP2D6 polymorphisms have been described to the moment, the frequency of many of them is relatively low (≤ 1%). 10 The most common variant of the CYP2D6 gene causing an absence of the enzymatic activity is the 1846A ( CYP2D6*4 ) allele ( rs3892097 ). 11 It was formed because of single nucleotide replacement 1846G>A in the genomic DNA sequence (NCBI Reference Sequence: NG_008376.3).…”
Section: Introductionmentioning
confidence: 99%